Access and quality of the assistance given to the disabled people in the public health services in Campinas county - Toldrá, Rosé Colom; Pérez, Marco Antonio Gomes; Matta, Mareia Aparecida Piccoloto (Revista de Terapia Ocupacional da Universidade de São Paulo, 2000)
This study aims at analysing the access and quality of the assistance given to the disabled people in the public health services in Campinas - SP, Brazil. Four types of questionnaires, containing qualitativo and quantitativo questions, were elaborated as the research instrument and applied to health professionals in the major public health services, at basic, specialized and hospital assistance. The results show social exclusion of the disabled people, demonstrated by the difficulties of obtaining assistance and the existence of architectonic barries in these services. It were also observed repressed demand, and deficiency of human and material resources, both interpretated as causes of low access. Of ali 34 inquired services, 32 referred any kind of architectonic barrier. The information obtained from the reserach conclude low access and prejudices of quality of the health assistance given to this specific population and, consequently damage to its quality of life.